AB0326 Does the achievement of remission in early rheumatoid arthritis depend on the age?. (23rd January 2014) - Bradna, P.; Soukup, T.; Bastecka, D.; Toms, J.; Kodeda, M.
Abstract : Objectives: Higher age belongs to unfavorable factors in most of prognostic algorithms in rheumatoid arthritis. Aims of study were to verify the impact of age on achievement of clinical remission in early and very early rheumatoid arthritis. Methods: 92 patients with early rheumatoid arthritis (ACR/EULAR criteria 2010) were treated by DMARDs according to Treat to target method. Remission was evaluated after 12 months of treatment by the DAS28≤2, 6, and according to ACR/EULAR provisional definition of remission (SDAI and Boolean methods). Low disease activity was assessed by DAS28≤3, 2. We have investigated clinical (number of swollen joints, visual scale of activity) laboratory (ESR and CRP), immunological markers (Rf's, ACPA) and x-ray of hand and foot joints. Results: 49 patients were younger then 60 and 46 of them were older. Both groups get to remission in the same proportion (47 vs 51%). Patients, who reached remission, had shorter history (p=0, 03), other entry parameters were the same. Younger group had more frequently positive autoantibodies (ACPA 72 vs 26% p=0, 02; RF 90 vs 33% p=0, 03). There were more very early arthritis patients (81 vs 40%) in the younger group. Younger patients had higher entry CRP (p=0, 05) and none significantly higher ESR. In younger patients there also was higher chance to ACR/EULAR remission Boolean criteria (p=0, 002) Conclusions: Age in the beginning of arthritis did not affect significantly chance to achieve remission in 12 months of early and very early rheumatoid arthritis therapy. More relevant it is the time from beginning of arthritis to start of therapy; significantly better results were in first 3 months of arthritis. Younger patients, who reached remission, have more frequent autoantibodies (ACPA and RF). There was no significant difference in presence of auto antibodies between successful patients and patients, who did not achieve remission. References: Hider SL, Silman AJ, Thomson W et al: Ann Rheum Dis. 2009 Jan;68(1):57-62. Disclosure of Interest: None Declared